IDENTIFICATION OF FACTORS AFFECTING AGRICULTURAL LAND COVER CHANGE IN KARAWANG REGENCY WITH GEOGRAPHICALLY WEIGHTED REGRESSION (GWR) ANALYSIS - Hutahaean, Michael
Karawang Regency is a regency in West Java that acts as a rice granary in West Java as well as carrying out the task of maintaining national food security. However , population growth and rapid growth of the industrial sector in Karawang Regency have an impact on the conversion of agricultural land so that it can threaten the role of Karawang Regency in maintaining food security both at the provincial and national levels. This study aims to identify the factors that influence the conversion of agricultural land in Karawang Regency. The data used in this study is secondary data consisting of Landsat 8 satellite imagery, spatial data from the Geospatial Information Agency (BIG), and statistical data from the Central Statistics Agency (BPS). The methodology used in this research is descriptive analysis, exploratory regression analysis, Ordinary Least Square (OLS), and Geographically Weighted Regression (GWR). The results of the analysis show that there is a change in the area of agricultural land cover in 2015-2021 of 187.14 km2. The largest change in agricultural land cover occurred in Telukjambe Barat District, which was 16.57 km 2, while the smallest change in agricultural land cover occurred in Tirtajaya District, which was 0.59 km2. In addition, there are two variables that significantly influence in explaining the factors that affect the conversion of agricultural land in Karawang Regency, namely the variable length of the road and the variable distance from the sub -district to the center of Karawang Regency. It is also concluded that the GWR model is the best model in explaining the analysis of the factors that affect the conversion of agricultural land in Karawang Regency.